OsOLP1 contributes to drought tolerance in rice by regulating ABA biosynthesis and lignin accumulation - Yan, Jianpei; Ninkuu, Vincent; Fu, Zhenchao; Yang, Tengfeng; Ren, Jie; Li, Guangyue; Yang, Xiufen; Zeng, Hongmei (Frontiers in Plant Science, 2023)
Rice, as a major staple crop, employs multiple strategies to enhance drought tolerance and subsequently increase yield. Osmotin-like proteins have been shown to promote plant resistance to biotic and abiotic stress. However, the drought resistance mechanism of osmotin-like proteins in rice remains unclear. This study identified a novel osmotin-like protein, OsOLP1, that conforms to the structure and characteristics of the osmotin family and is induced by drought and NaCl stress. CRISPR/Cas9-mediated gene editing and overexpression lines were used to investigate the impact of OsOLP1 on drought tolerance in rice. Compared to wild-type plants, transgenic rice plants overexpressing OsOLP1 showed high drought tolerance with leaf water content of up to 65%, and a survival rate of 53.1% by regulating 96% stomatal closure and more than 2.5-fold proline content promotion through the accumulation of 1.5-fold endogenous ABA, and enhancing about 50% lignin synthesis. However, OsOLP1 knockout lines showed severely reduced ABA content, decreased lignin deposition, and weakened drought tolerance. In conclusion, the finding confirmed that OsOLP1 drought-stress modulation relies on ABA accumulation, stomatal regulation, proline, and lignin accumulation. These results provide new insights into our perspective on rice drought tolerance.